The invitation [videorecording (DVD)] - Butler, Blair; Emmanuel, Nathalie, 1989-; Doherty, Thomas (Actor); Corneliussen, Stephanie, 1987-; Boden, Alana; Skinner, Hugh, 1985-; Pertwee, Sean (Sony Pictures Home Entertainment, 2022)
A young woman is wooed and swept off her feet, only to realize a gothic conspiracy is stirring.